Contribution of Zakat Institutions to the Strengthening and Development of Islamic Religious Education in Indonesia - Ilma, Miftahul; Pratiwi, Audya; Ningtias, Risky Cahya (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
Zakat, as one of the pillars of Islam, is not only an act of worship but also holds substantial potential as a source of social and economic funding, particularly in supporting the education sector. This study aims to explore the role of zakat in achieving the goals of Islamic education in Indonesia, focusing on improving quality, inclusivity, and equity in education. The research adopts a qualitative approach with a literature review method, where data are sourced from books, scientific articles, and journals. The findings reveal that zakat can be a sustainable funding mechanism for enhancing access to Islamic education, particularly in underprivileged communities. Properly managed zakat funds have been shown to support scholarship programs, infrastructure development, and various educational initiatives, which directly contribute to raising educational standards across the country. This study contributes to the growing discourse on zakat's strategic role in education by providing insights into how its optimization can serve as a cornerstone for developing an inclusive and balanced Islamic education system in Indonesia. By highlighting the transformative potential of zakat, this research underscores the need for effective zakat management and collaboration among stakeholders to realize its full benefits for the education sector